Synthesis without meta-analysis (SWiM) in systematic reviews: reporting guideline - Campbell, Mhairi; McKenzie, Joanne E; Sowden, Amanda; Katikireddi, Srinivasa Vittal; Brennan, Sue E; Ellis, Simon; Hartmann-Boyce, Jamie; Ryan, Rebecca; Shepperd, Sasha; Thomas, James; Welch, Vivian; Thomson, Hilary (BMJ (Online), 2020)
In systematic reviews that lack data amenable to meta-analysis, alternative synthesis methods are commonly used, but these methods are rarely reported. This lack of transparency in the methods can cast doubt on the validity of the review findings. The Synthesis Without Meta-analysis (SWiM) guideline has been developed to guide clear reporting in reviews of interventions in which alternative synthesis methods to meta-analysis of effect estimates are used. This article describes the development of the SWiM guideline for the synthesis of quantitative data of intervention effects and presents the nine SWiM reporting items with accompanying explanations and examples.